Literasi Digital dan Kemampuan Menulis Argumentasi Siswa SMA - Irawan, Nayshila; Ar, Lisda Yanti; Salmia, Salmia; Amalia, Niszla Rina; Oktaviana, Ressa; Anhar , Anhar (Indo-MathEdu Intellectuals Journal, 2025)
Digital literacy is an important skill that high school students must have in order to cope with rapid technological developments and the flow of information. This skill involves not only the ability to access and use technology, but also the ability to analyze, evaluate, and manage information critically and ethically. In the context of language learning, digital literacy plays a major role in argumentative writing skills, as writing requires students to process information, think logically, and form opinions based on valid data. This study aims to analyze the relationship between digital literacy and argumentative writing skills in high school students. The method used was a literature study with a descriptive approach, which examined various previous research results related to the influence of digital literacy on writing skills. The results of the study show that students with high levels of digital literacy have better argumentative writing skills. This can be seen from their ability to select credible sources of information, avoid fake news, and construct logical and evidence-based arguments. These findings emphasize the importance of integrating digital literacy into language learning in secondary schools so that students can write critically, responsibly, and in a manner relevant to the demands of the 21st century.